PENGARUH MEDIA LAGU LASKAR PELANGI TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS X - Nurul Wasih Asih; Wienike Dinar Pratiwi; Roni Nugraha Syafroni (Jurnal Education and Development, 2022)
This study aims to determine the effect of the media song "Laskar Pelangi" on the ability to write poetry of class X students at Senior High School Negeri 1 Gantung. The approach used in this study is a quantitative approach, with an experimental method. To obtain data, this research was carried out by means of a poetry writing test, and answering questionnaires. The samples used in the study were taken 2 classes, namely class XIPS 3 and X IPS 4. Class IPS 3 as the experimental class while class X IPS 4 became the experimental class. The results showed that the media song "Laskar Pelangi", had an effect on students' poetry writing skills, seen from the increase in the average score from pre-test to post-test, which at the beginning was 74.93 after receiving treatment to 77.33. The results of the analysis also shows the value of sig (2 –tailed) 0.001 < 0.05, which means that the media of the song is influential. There are also differences in the ability of classes taught with song media and not using song media. The control class has a post-test score of 75.4 while the experimental class has 77.33. The results of the analysis also show the value of sig (2 –tailed) 0.016 < 0.05, so there is a difference in the average ability of the two classes. Both results of the analysis were supported by the answers to the student questionnaires who responded well to the media song "Laskar Pelangi".